Bram Stoker's Dracula : a reader's guide - Hughes, William, 1964- (Continuum reader's guides., 2009)
Dracula (1897) is one of the most commonly studied gothic novels and has been hugely influential through adaptations in fiction, on stage and in cinema.¨Offering an authoritative, up-to-date guide for students, this book introduces its context, language, themes, criticism and afterlife, leading students to a more sophisticated understanding of the text.È. This is the ideal guide to reading and studying the novel, setting Dracula in its historical, intellectual and cultural contexts, offering analyses of its themes, style and structure, providing exemplary close readings, presenting.